Effect of feeding methods of katuk (Sauropus androgynus) extract on performance and carcass quality of broiler chickens - U Santoso; T Suteky; Heryanto .; Sunarti . (Indonesian Center for Animal Research and Development (ICARD), 2002)
The present experiment was conducted to evaluate effect of feeding methods of katuk extract on performance and carcass quality of broilers. Sixty 20-d-old male broilers were distributed to 5 treatment groups of 4 replicates with 3 birds each. One treatment group was fed basal diet without katuk extract (P0), whereas other treatment groups were fed basal diet plus 18 g katuk extract/kg diet (P1), basal diet plus 9 g katuk extract/l drinking water (P2), basal diet plus 9 g katuk extract/kg diet plus 4.5 g katuk extract/l drinking water (P3), and basal diet plus 4.5 g katuk extract/kg diet plus 2.25 g katuk extract/l drinking water (P4). Experimental results showed that weight gain of P1 and P4 were significantly higher (P<0.05) than those of P0 and P2. Feed conversion ratio of P1 and P4 were significantly lower than those of P0 and P2 (P<0.05). Feed intake, water intake, the weights of heart, liver and gizzard were not significantly different (P>0.05), but the weight of intestine was significantly affected (P<0.05) Abdominal fat of P4 was significantly lower than that of P0, P1 and P2 (P<0.05). Carcass color of P4 was significantly better than that of P0, P1, P2 and P3 (P<0.01). Katuk extract feeding had no effect on smell and taste of meat (P>0.05). P4 had better meat color than P0, P1, dan P2 (P<0.05). Katuk extract feeding had no effect on meat bone ratio, carcaas weight and cooking loss (P>0.05). In conclusion, in order to improve performance and carcass quality, broiler chickens could be given katuk extract through diet plus drinking water at level of 4.5 g/kg diet plus 2.25 g/l drinking water. Key words: Katuk extract, performance, carcass quality, abdominal fat